High-Altitude Wild Species Solanum arcanum LA385—A Potential Source for Improvement of Plant Growth and Photosynthetic Performance at Suboptimal Temperatures - Dinh, Quy-Dung; Dechesne, Annemarie; Furrer, Heleen; Taylor, Graham; Visser, Richard G. F.; Harbinson, Jeremy; Trindade, Luisa M. (Frontiers in Plant Science, 2019)
Plant growth, development and yield of current tomato cultivars are directly affected by low temperatures. Although wild tomato species have been suggested as a potential source for low temperature tolerance, very little is known about their behaviour during the reproductive phase. Here we investigated the impact of suboptimal temperatures (SOT, 16/14˚C), as compared to control temperatures (CT, 22/20˚C), on plant growth, photosynthetic capacity, and carbohydrate metabolism. Under these conditions, two genotypes were analysed: a Solanum lycopersicum cultivar Moneymaker and a high altitude wild species Solanum arcanum LA385, from flowering onset until a later stage of fruit development. Total dry matter production in cv Moneymaker was reduced up to 30% at SOT, whereas it was hardly affected in wild accession LA385. Specific leaf area, total leaf area, and number of fruits were also decreased at SOT in cv Moneymaker. In contrast wild accession LA385 showed an acclimation to SOT, in which ΦPSII and net CO2 assimilation rates were less affected, a similar specific leaf area, higher total leaf area, and higher number of fruits compared to those at CT. In addition, LA385 appeared to have a more distinct sucrose metabolism than cv Monemaker at both temperatures, in which it had higher contents of sucrose-6-phosphate, sucrose, and ratio of sucrose: starch in leaves and higher ratio of sucrose: hexose in fruits. Overall our findings indicate that wild accession LA385 is able to acclimate well to SOT during the reproductive phase, whereas growth and development of cv Moneymaker is reduced at SOT..